GENDER-SPECIFIC FUNCTIONAL PROFILES IN OUTPATIENT GERIATRIC REHABILITATION: TOWARDS A PERSONALIZED MULTICOMPONENT MODEL - Musaeva O.T.,; Khalilova B.R., (Central Asian Journal of Medicine, 2025)
The article presents the results of an outpatient study on functional deficits in elderly patients, with a focus on gender differences and personalized approaches to rehabilitation. The research was conducted using a structured clinical-functional evaluation of 247 geriatric patients (135 women and 112 men) aged 60 and older. Validated scales were applied, including MMSE, MoCA, BDI, MNA, TUG, Barthel Index, and SF-36. The study included analysis of physical, cognitive, emotional, nutritional, and social impairments, stratified by sex and age. The findings revealed significant gender-related differences: women were more likely to experience depression, malnutrition, and loneliness, while men demonstrated higher rates of sarcopenia, cognitive decline, and mobility disorders. Implementation of a gender-sensitive rehabilitation model resulted in significant improvement across multiple indicators (p < 0.05), emphasizing the need for differentiated ambulatory care strategies.